Newborn Interneurons in the Accessory Olfactory Bulb Promote Mate Recognition in Female Mice - Oboti, Livio; Schellino, Roberta; Giachino, Claudio; Chamero, Pablo; Pyrski, Martina; Leinders-Zufall, Trese; Zufall, Frank; Fasolo, Aldo; Peretto, Paolo (Frontiers in Neuroscience, 2011)
In the olfactory bulb of adult rodents, local interneurons are constantly replaced by immature precursors derived from the subventricular zone. Whether any olfactory sensory process specifically relies on this cell renewal remains largely unclear. By using the well-known model of mating-induced imprinting, we demonstrate that this olfactory memory formation critically depends on the presence of newborn granule neurons in the accessory olfactory bulb. Accordingly, we show that, in adult female mice, exposure to male pheromones increases the number of new granule cells surviving in the accessory olfactory bulb. This neuronal addition depends on the detection of sensory cues by the vomeronasal organ and requires centrifugal feedback activity from the amygdala. The stimuli affecting neuronal survival are contained in the low molecular weight fraction of urine and are implied in pheromonal recognition during mating. By chemical depletion of newly generated bulbar interneurons, we show a direct role of renewed granule cells in the accessory olfactory bulb in preventing pregnancy block by mating male odours. Taken together, our results indicate that adult neurogenesis is essential for specific brain functions such as persistent odour learning and mate recognition.